Low Impact Development Intensive Rural Construction Planning in Xu Fu Village Ningbo, China: Planning Review through Rural Resilience Perspective - Roosmayri Lovina Hermaputi; Chen Hua (Jurnal Wilayah dan Lingkungan, 2017)
Xu Fu Village Ningbo LID Intensive Rural Construction Planning is a cooperation project between Zhejiang University and Ningbo Institute of Technology which named "12th Five-Year National Science and Technology support program-the comprehensive demonstration of the key technology of the beautiful rural construction in the rapid urbanization area of the Yangtze River Delta". This plan focuses on intensive rural construction as part of rural development and construction project that applies the principles of low impact development. Xu Fu Village located in the Yangtze River Delta Region. Currently, the rural growth brings the high impact of development, as a result of rapid urbanization growth arising several issues, such as low land use efficiency, dispersed rural residence, homestead occupies more, rural roads covering over, etc. Meanwhile, Xu Fu village wishes to develop its tourism potential. Thus, the intensive rural construction should be done to avoid the severe effect. The project result hopefully can improve the quality and level of rural residential planning, design, and construction; improve their living environment; save construction land and water use; and improve energy efficiency. The aim of this study is to review the Low Impact Development (LID) Intensive Rural Construction in Xu Fu Village, Ningbo City through the rural resilience perspective. This paper will describe the project plan first, then review it through rural resilience perspective. This paper will elaborate the rural resilience theory and then review the rural resiliency through two parts; the first part is identifying rural resilience in rural infrastructure development based on the criteria created by Ayyob S. and Yoshiki Y. (2014), about urban resiliency criteria, and then the second part is reviewing Xu Fu Village resilience through Arup Resilience Qualities (2012), considering three rural resilience domain (economy, ecology, and cultural).